2012
DOI: 10.1155/2012/572484
|View full text |Cite
|
Sign up to set email alerts
|

Taenia saginata: A Rare Cause of Gall Bladder Perforation

Abstract: We report a case of biliary peritonitis caused by gall bladder perforation due to Taenia saginata induced gangrenous cholecystitis. Although parasites are not unusual causes of biliary tract disorders, especially in disease endemic areas, but this is for the first time that Taenia saginata has been reported to cause gall bladder perforation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 13 publications
0
17
1
Order By: Relevance
“…Hakeem et al [7] presented a case of gall bladder perforation in 2012. A case of colonic anastomotic leakage related to T. saginata infestation following a right hemicolectomy procedure was reported by Sozutek et al [1] in 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Hakeem et al [7] presented a case of gall bladder perforation in 2012. A case of colonic anastomotic leakage related to T. saginata infestation following a right hemicolectomy procedure was reported by Sozutek et al [1] in 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal taeniosis is generally asymptomatic (Garcia et al, 2003), although mild abdominal discomfort has been reported (Tembo and Craig 2015). Rare reported sequale to intestinal taeniosis include Cholangitis (an infection of the biliary tract) (Uygur-Bayramicli et al, 2012), gall bladder perforation (Hakeem et al, 2012), appendicitis (Kulkarni et al, 2014) and bowel obstruction (Atef and Emna, 2015;Li et al, 2015). Some people suffering from taeniosis will notice the passage of proglottids (parasite segments containing eggs) in their faeces, although this seems most common with the more motile proglottids of T. saginata (Garcia et al, 2003).The major health burden imposed by T. solium is human cysticercosis caused by the ingestion of eggs, or via auto-infection within individuals with taeniosis, and the subsequent aberrant encystment of the larval stage within humans.…”
Section: Symptomatologymentioning
confidence: 99%
“…However, it has been shown in the literature that they may require surgical interventions due to obliterations in appendices or biliary or pancreatic ducts. [4][5][6] Sheikh et al reported that a 6.3-m-long T. saginata was released from the nose of a female patient. [7] In the present case, T. saginata proglottids were released from the patient's nose and anus.…”
Section: Most Patients Carrying Tapeworms Have No Symptomsmentioning
confidence: 99%